Implicature Of Request Expressions In Animation Movie Script Entitled Finding Nemo - Sundari, Eka, Dra. Siti Zuhriah Ariatmi,M.Hum (2017)
This study aimed to describe the form of request strategies, the implicature of the request expressions and the maxim violation of request expressions used in Finding Nemo movie.This research belongs to descriptive qualitative research. The data are all of the request expressions in Finding Nemo manuscript. The way to collect the data, the writer uses documentation and observation toward the Finding Nemo movie. The results of the research show that: 1) From 122 request expressions that found in this research, those can be divided into seven request strategies: there are 19 data or 15,6% of hints, 18 data or 14,7% of ability/willingness, 2 data or 1,6% of suggestory formulae, 3 data or 2,5% of wishes, 4 data or 3,3% of desires/needs, 22 data or 18% of obligation and 54 data or 44,3% of imperatives, 2) From 22 numbers data, there are 1 datum of conventional implicature (4,5%) and 21 data that belong to conversational implicature (95,5%), 3) From 21 data of conversational implicature, there are 14 data that violate the maxim. There are 5 data that violate the maxim of quantity (35,8%), 7 data violates the maxim of quality (50%), 1 datum violates the maxim of relevance (7,1%), and 1 datum violates the maxim of manner (7,1%). Keywords: request expressions, request strategies, implicature, maxim violation.